A Rare Iatrogenic Reaction to Allopurinol - Carvalho e Branco, Joana; Gomes, A. Filipa; Dutschmann, Rita; Dutschmann, Luís (Portuguese Journal Internal Medicine, 2015)
There are very few case reports of iatrogenic bone marrow granuloma induced by allopurinol. Granulomas are a rare finding on bone marrow biopsies and can have numerous etiologies, namely infectious, neoplastic, autoimmune, drug related or sarcoidosis. In the absence of pathognomonic features, the combination of clinical, laboratorial, image and histological data is essential to establish a diagnosis. We report a case of a 59 year-old Caucasian, referred to Internal Medicine consultation for gout, an medicated with allopurinol and colchicine. Through his follow-up anemia and thrombocytopenia emerged. Myelogram and bone marrow biopsy revealed “numerous epithelioid granulomas, without multinucleated giant cells, without the identification of microorganisms on PAS diastase stain or Ziehl-Neelsen, without neoplastic cells, consistent with a granulomatous myelitis.” The proposed etiology was a drug hypersensitivity reaction to allopurinol so it was discontinued. The exam was repeated a year later and no granulomas were observed, which confirmed the diagnosis.